Mali's Infrastructure : A Continental Perspective - Briceno-Garmendia, Cecilia M.; Dominguez, Carolina; Pushak, Nataliya (2012)
Despite external shocks, Mali's economy grew by 5.3 percent per year between 2003 and 2006, driven primarily by the telecommunications sector. But Mali's landlocked condition, together with the uneven distribution of population and economic activities between the arid north and the much richer south, defy the country's ability to sustain this pace of growth. Mali depends heavily on regional infrastructure and transport corridors. A strategic focus on regional integration has paid off, and critical institutional decisions are bringing many positive developments. But Mali still faces infrastructure challenges, the starkest of which lies in the power sector. The cost of producing power in Mali is among the highest in the region, with the result that only around 17 percent of the population has access to electricity, much lower than in other low-income African countries. The water and sanitation sectors also represent a challenge, as the nation works to separate the power and water-and-sanitation functions of EDM, the multisector utility. Mali spent about $555 million per year on infrastructure during the late 2000s. A total of $200 million is lost annually to inefficiencies. Assessing spending needs against existing spending and potential efficiency gains leaves an annual funding gap of $283 million per year.Mali will likely need more than a decade to reach the illustrative infrastructure targets outlined in this report. Under business-as-usual assumptions for spending and efficiency, it would take over 50 years for Mali to reach these goals. Yet with a combination of increased finance, improved efficiency, and cost-reducing innovations, it should be possible to reduce that time to 15 years.